As cordas vibrantes: uma sugestão contextualizada no ensino de Matemática e Física - Paulo, Leonardo Martins de (Universidade Federal de São Carlos, 2022)
The purpose of this work is to carry out a research of both historical and scientific concepts, related to the waves produced by vibrating strings. During the preparation of the text, a bibliographic and theoretical survey was carried out on the main researchers of the subject, and the motivations for the discoveries in the field of music and science, thus strengthening the debate and deepening of the theme. In the first pages, the observation made by Pythagoras and his school is reported, referring to the stretched string when placed to vibrate, producing sounds in different frequencies. Since then, the participation of mathematics in this movement, or even in the various later times and different chapters of history, involved ideas, thinkers, and theories that developed over the centuries, such as the wave equation. Next, as an emphasis on the evolution of the concepts exposed and argued, a theoretical-practical application will also be made, where the examples presented and discussed through the Fourier equation are directly connected in this scope. We also suggest, in a didactic way, the construction of a lesson plan, composed of questions from recent entrance exams, where the objective is to lead the student to critical thinking, facing the analysis and solving of exercises in diverse and complex contexts, thus strengthening the debate and enrichment of the teaching and learning process.
The vibrating strings: a contextualized suggestion for teaching Mathematics and Physics
Las cuerdas vibrantes: una sugerencia contextualizada para la enseñanza de las Matemáticas y la Física
Keywords: Vibração de cordas esticadas; Equação de ondas; História; Plano de aula; Situações-problema; Vibration of stretched strings; Wave equation; Story; Class plan; Problem situations; CIENCIAS EXATAS E DA TERRA::MATEMATICA